Quranic Generation: Community Service Program Develops Al-Quran Education Park - Putri, Lusiana Rahmadani; Kamaluddin, Kamaluddin; Aziz, Saifiullah (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background. The community service program in Indonesia has become an important part of efforts to build a better community, including in the context of Al-Qur'an education. community service program activities can be an effective means to develop the potential of the younger generation in understanding and practicing the Al-Qur'an.Purpose. This study aims to explore the effectiveness of the community service program program in fostering Al-Qur'an Education Parks as an effort to strengthen the understanding and practice of the Al-Qur'an among the younger generation.Methods. This study uses a qualitative approach with case studies, involving data collection through participatory observation and in-depth interviews with community service program participants and managers of Al-Qur'an Education Parks.Results. The results of the study indicate that the community service program program is effective in improving the understanding and practice of the Al-Qur'an among the younger generation, with increased active participation in learning activities and religious life.Conclusions. The community service program can be used as a useful model in fostering Al-Qur'an Education Parks, by emphasizing the integration of Al-Qur'an values in the daily lives of the younger generation.